PENGELOMPOKAN TINGKAT KRIMINALITAS DENGAN METODE AGGLOMERATIVE DAN K-MEANS SERTA PEUBAH PENCIRINYA - TARAM, NYOMAN GDE PRAJNAWIWEKA RATMASA; SUKARSA, I KOMANG GDE; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika; Vol 8 No 2 (2019), 2019)
The purpose of this research is it define the classification of crime rate based on the type of crime and its characterization variable. The data used in this research are secondary data in form of data on the number of crime rates based on the type of crime in 32 regional police in the province with 12 variables. This research is used Agglomerative and K-Means method along with Biplot Analysis. The result shows that there are three classification based upon Single Linkage as the best method which each characteristic of every classification is the crime of family abuse, crime of minor mistreatment and crime of corruption.